A cell-free biosensor for multiplexed and sensitive detection of biological warfare agents - Park, Yu Jin; Choi, Sunjoo; Lee, Kyung Won; Park, So Yoon; Song, Dong Yeon; Yoo, Tae Hyeon; Kim, Dong Myung (Biosensors and Bioelectronics, 2024)
The rapid and precise detection of pathogenic agents is critical for public health and societal stability. The detection of biological warfare agents (BWAs) is especially vital within military and counter-terrorism contexts, essential in defending against biological threats. Traditional methods, such as polymerase chain reaction (PCR), are limited by their need for specific settings, impacting their adaptability and versatility. This study introduces a cell-free biosensor for BWA detection by converting the 16S rRNA of targeted pathogens into detectable functional protein molecules. The modular nature of this approach allows for the flexible configuration of pathogen detection, enabling the simultaneous identification of multiple pathogenic 16S rRNAs through customized reporter proteins for each targeted sequence. Furthermore, we demonstrate how this method integrates with techniques utilizing retroreflective Janus particles (RJPs) for facile and highly sensitive pathogen detection. The cell-free biosensor, employing RJPs to measure the reflection of non-chromatic white light, can detect 16S rRNA from BWAs at femtomolar levels, corresponding to tens of colony-forming units per milliliter of pathogenic bacteria. These findings represent a significant advancement in pathogen detection, offering a more efficient and accessible alternative to conventional methodologies.
Keywords: 16S rRNA; Biological warfare agents; Cell-free; Cell-free biosensor; Micro particles; Molecular converter; Molecular diagnostics; Multiplexed detection; Nucleic acid test; Retroreflective janus microparticle; Bacteria; Biological Warfare Agents; Biosensing Techniques; Cell-Free System; Humans; Limit of Detection; RNA, Ribosomal, 16S; Cell-free biosensor; Molecular converter; Molecular diagnostics; Multiplexed detection; Nucleic acid test; Retroreflective Janus microparticles